1998
DOI: 10.1292/jvms.60.815
|View full text |Cite
|
Sign up to set email alerts
|

Local Disappearance of Epiphyseal Growth Plates in Rats with Hypervitaminosis A.

Abstract: ABSTRACT. Epiphyseal growth plates of proximal tibiae in rats with high doses of vitamin A (V-A) were observed. Of 4 groups, each consisting of 5 rats, three groups were given V-A at doses, IU/100 g by body weight/day, of 50,000, 100,000, and 150,000, respectively. The other group rats were given no V-A (control). Rats were administered V-A for the 5 days from 4 weeks after birth and sacrificed at 12 weeks after birth. Three rats of the 150,000 IU group died during the period of observation. The decalcified se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
2
13
0
1
Order By: Relevance
“…In the present study, the highly calcified cartilage matrix, which was distinguished as granular high BSE signals [11] or the basophilic granules by HE staining [14], was detected within the epiphyseal growth plate in VA rats on Day 12. Such calcified cartilage matrix contained large calcospherulites in VA rats, but did not contain them in the hypertrophic zone in control rats.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the present study, the highly calcified cartilage matrix, which was distinguished as granular high BSE signals [11] or the basophilic granules by HE staining [14], was detected within the epiphyseal growth plate in VA rats on Day 12. Such calcified cartilage matrix contained large calcospherulites in VA rats, but did not contain them in the hypertrophic zone in control rats.…”
Section: Discussionmentioning
confidence: 82%
“…The focal disappearance of the epiphyseal growth plate, i.e., premature closure of the epiphyseal growth plate, is regarded as the characteristic conformational feature in bovine Hyena disease and hypervitaminosis A [2-5, 18, 20]. In our previous study [11], we suggested that the high calcification of cartilage matrix in the epiphyseal growth plate was closely related to the focal disappearances of the epiphyseal growth plate, although the detailed process of the focal disappearance still remains unclear. In our recent study [17], we, therefore, experimentally administered a high dose of vitamin A to young rats to investigate the cellular and matrical alterations chronologically and demonstrated that initial disorders in the epiphyseal growth plate were attributed to the disturbance caused by a high dose of VA in the differentiation of chondrocytes.…”
mentioning
confidence: 99%
“…In rats, vitamin A toxicity causes calcification of the epiphyseal-resting zone, with subsequent, complete disappearance of the growth plate [7,9]. In calves, vitamin A toxicity results in “hyena disease,” where premature epiphyseal closure of the hind limbs and the ensuing abnormal growth results in a gait disturbance resembling hyenas [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…These defects manifest as an acquired chondrodysplasia in experimental animal models given high doses of vitamin A, with growth plate thinning, premature ossification of column cartilage and markedly reduced longitudinal bone growth even before premature growth plate closure [3,7-9], likely through wnt/catenin pathway activation or antagonizing Fibroblast Growth Factor Receptor (FGFR) signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Outras pesquisas também descreveram uma diminuição do disco epifisário mediante um excesso de vitamina A (CLARK, 1970;CLARK;SEAWRIGHT, 1968;CLARK;GARTNER, 1970;DOIGE;SCHOONDERWOERD, 1988;KODAKA et al, 1998;SOETA et al, 1999). Soeta et al (1999) demonstrou que doses elevadas de vitamina A em ratos ocasiona uma disfunção dos condrócitos resultando na deformação e na diminuição da espessura do disco epifisário.…”
Section: Resultsunclassified